Ambliopía estrábica en paciente de 8 años. - Gavilanes Moreno, Steven Ricardo (2023)
The present study on a case of strabismic amblyopia is based on analyzing the severity of the ocular condition in an 8-year-old patient, through the application of complementary tests that are applied for the definitive diagnosis, it allows obtaining the necessary information to achieve the application of optometric treatments. with the purpose of improving visual acuity, visual capacity, and ocular vision, in addition to reducing the risks of complications in the sense of vision. Regarding the data obtained from the examinations, the use of lenses and eye patches were applied as a treatment to reduce complications due to amblyopia and strabismus. It is important to indicate that amblyopia is the reduction of visual acuity either in one eye or in due to the deficit in visual development, this condition can be treated if it is detected in time. In strabismus it is based on the deviation of an ocular axis, it is very frequent in pediatric patients, it has aesthetic consequences, the alteration of visual acuity, for which it is important to indicate an initial treatment. In conclusion, using optometric exploration techniques in conjunction with the treating ophthalmologist, it was possible to diagnose strabismic amblyopia by the application of tests such as retinoscopy, retinal examination, refraction tests, Hirschberg test, test cover uncover, which were essential to establish a definitive diagnosis.